Rousseau on Education, Freedom, and Judgment - Schaeffer, Denise, 1968- (Book collections on Project MUSE., 2014)
"Explores the writings of Rousseau, including Emile, Discourse on the Origins of Inequality, and On the Social Contract, focusing on the problem of judgment and its role in creating the condition for genuine self-rule"--Provided by publisher